Interdepartmental Communication Increases Organizational Performance Keeping HRM as a Mediating Variable - Gondal, Uzma Hanif; Shahbaz, Muhammad (Journal of Asian Business Strategy, 2012)
The current study addresses the importance of Human Resource Management (HRM) and implication of its widely used practices. We tested the relationship of Interdepartmental Communication with Organizational Performance using Human Resource Management (HRM) as a mediator. A cross-sectional study was conducted and data was collected through survey questionnaire method from 200 respondents in three different multinational organizations (Telenor, Silk Bank and CureMD). Using Linear Regression Model, we found HRM to be strongly mediating the relationship of Interdepartmental Communication and Organizational Performance. Further areas for future research and implications are also highlighted.